Ética e voluntariado no serviço social - Alves, Luciano (2010)
The dissertation deals with ethical aspects related to the reproduction of religious values, in nature and origin, of the volunteer social worker. Is based on Marxist tradition of Social Work in Brazil with regards to the development of the Political- Ethical Professional Project. Presents the connections between the profession s theoretical scope and the contemporary volunteering socio-historical assumptions, trying to rationalize the controversial aspects resulting in the reality revelation. Offers support for a secular debate about the charity s moral values in the situations that involves volunteer social work, as well as indicates for further studies on ethical grounds in face of the work category in contemporary capitalism. It presents qualitative research matured as result of previous studies about the relationship between the profession and the religious institutions, and the Social Work learner s profile that involves the professional training and religiosity. This research analyses, lastly, the delineate tints of the profession practiced without payment, addressing its interfaces with the work s precariousness, with the social problems depoliticization in capitalist society and the ethical and political praxis of social worker s complexities